General Construction of Chameleon All-but-one Trapdoor Functions - LIU, Shengli (Institutional Knowledge at Singapore Management University, 2011)
Lossy trapdoor functions enable black-box construction of public key encryption (PKE) schemes secure against chosen-ciphertext attack [18]. Recently, a more efficient black-box construction of public key encryption was given in [13] with the help of chameleon all-but-one trapdoor functions (ABO-TDFs). In this paper, we propose a black-box construction for transforming any ABO-TDFs into chameleon ABO-TDFs with the help of chameleon hash functions. Instantiating the proposed general black-box construction of chameleon ABO-TDFs, we obtain the first chameleon ABO-TDFs based on the Decisional Diffie-Hellman (DDH) assumption.